2021
DOI: 10.3857/roj.2020.01074
|View full text |Cite
|
Sign up to set email alerts
|

Salvage proton beam therapy for locoregional recurrence of non-small cell lung cancer

Abstract: Purpose This study aimed to evaluate the clinical outcomes and toxicities of salvage proton beam therapy (PBT) in patients with locoregional recurrent non-small cell lung cancer (NSCLC). Materials and Methods We retrospectively reviewed 53 patients who received salvage PBT for locoregionally recurrent NSCLC between January 2016 and December 2019. The median clinical target volume (CTV) was 71.2 cm 3 (range, 13.3 to 1,200.7 cm 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…However, its outcome is similar to that of conventional RT or IMRT, and some studies have even reported higher toxicity rates of >40% [9]. Previously, our study on salvage PBT including 37 patients who underwent re-RT showed a 2-year OS of 79.2% and a grade 3 or higher toxicity rate of 18.9% [5], which included out-field thoracic recurrences.…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations
“…However, its outcome is similar to that of conventional RT or IMRT, and some studies have even reported higher toxicity rates of >40% [9]. Previously, our study on salvage PBT including 37 patients who underwent re-RT showed a 2-year OS of 79.2% and a grade 3 or higher toxicity rate of 18.9% [5], which included out-field thoracic recurrences.…”
Section: Introductionsupporting
confidence: 51%
“…The patients were initially diagnosed with NSCLC and underwent RT with curative intent. The patterns of failure after initial RT were considered as the inclusion criteria and were defined as follows: in-field failure, wherein the geometric center of the recurrent mass is within the 50% isodose line, and marginal failure, wherein it is within 25-50% of the isodose line [5,8]. Moreover, patients who underwent re-RT with curative intent were included in the study.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, proton therapy was tested in a special setting for locally advanced NSCLC, such as salvage, postoperative, or palliative manners. Shin et al [67] retrospectively reviewed 53 patients who received salvage proton therapy for locoregionally recurrent NSCLC, and found that the median disease-free interval was 14 months. The 2-year OS rate, local control rate, and PFS rate were 79.2%, 68.2%, and 37.1%, respectively.…”
Section: Locally Advanced Nsclcmentioning
confidence: 99%